2016
DOI: 10.1590/1413-81232015213.26572015
|View full text |Cite|
|
Sign up to set email alerts
|

Avaliação da qualidade da água de consumo por comunidades ribeirinhas em áreas de exposição a poluentes urbanos e industriais nos municípios de Abaetetuba e Barcarena no estado do Pará, Brasil

Abstract: assessment of the quality of water for consumption by river-bank communities in areas exposed to urban and industrial pollutants in the municipalities of abaetetuba and Barcarena in the state of Pará, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 12 publications
0
4
0
20
Order By: Relevance
“…Alternative processes like pyrite oxidation or acid rain, commonly found in industrial areas (Edmunds and Smedley, 1996), are unlikely to occur in the region. Other studies have detected low groundwater pH (around 4.5 -5.0) as a common feature in different places in the Amazon (Medeiros et al, 2016;Mendes et al, 2017).…”
Section: Physical Chemical Parameters and Chemical Composition Of Drimentioning
confidence: 90%
See 1 more Smart Citation
“…Alternative processes like pyrite oxidation or acid rain, commonly found in industrial areas (Edmunds and Smedley, 1996), are unlikely to occur in the region. Other studies have detected low groundwater pH (around 4.5 -5.0) as a common feature in different places in the Amazon (Medeiros et al, 2016;Mendes et al, 2017).…”
Section: Physical Chemical Parameters and Chemical Composition Of Drimentioning
confidence: 90%
“…These values are greater than our results for drinking water from deep wells (Schools B and D) and lower than those found from shallow wells (Schools A and C). Medeiros et al (2016) found high concentrations of N-NO3⁻ in shallow wells (7.7 -61.35 mg L -1 ) in riparian communities that were exposed to domestic and industrial pollutants elsewhere in the Amazon region.…”
Section: Physical Chemical Parameters and Chemical Composition Of Drimentioning
confidence: 93%
“…Embora se saiba que a qualidade da água varia em função da sazonalidade pluviométrica OLIVEIRA, 2014;KOLM et al, 2016;MEDEIROS et al, 2016) e que é importante conhecer a influência das chuvas na alteração das características físico-químicas e microbiológicas da água, não é objetivo desta pesquisa analisar a qualidade da água em período chuvoso para fins comparativos de resultados. Assim, este trabalho fica restrito à análise, discussão e entendimento da qualidade da água no ribeirão São Bartolomeu em período de seca, época em que a demanda de captação de água aumenta em função da ausência de chuvas.…”
Section: Amostragemunclassified
“…Foi encontrada contaminação fecal em todas as amostras avaliadas. Neste sentido, é importante reconhecer o monitoramento da qualidade da água como o instrumento de verificação da sua potabilidade para consumo humano, conforme padrão estabelecido na legislação (MEDEIROS et al, 2016).…”
Section: Introductionunclassified